Addition of Ascorbic Acid to the Extracellular Environment Activates Lipoplexes of a Ferrocenyl Lipid and Promotes Cell Transfection - Aytar, Burcu S. (2011)
The level of cell transfection mediated by lipoplexes formed using the ferrocenyl lipid bis(11-ferrocenylundecyl)dimethylammonium bromide (BFDMA) depends strongly on the oxidation state of the two ferrocenyl groups of the lipid (reduced BFDMA generally mediates high levels of transfection, but oxidized BFDMA mediates very low levels of transfection). Here, we report that it is possible to chemically transform inactive lipoplexes (formed using oxidized BFMDA) to “active” lipoplexes that mediate high levels of transfection by treatment with the small-molecule reducing agent ascorbic acid (vitamin C). Our results demonstrate that this transformation can be conducted in cell culture media and in the presence of cells by addition of ascorbic acid to lipoplex-containing media in which cells are growing. Treatment of lipoplexes of oxidized BFDMA with ascorbic acid resulted in lipoplexes composed of reduced BFDMA, as characterized by UV/vis spectrophotometry, and lead to activated lipoplexes that mediated high levels of transgene expression in the COS-7, HEK 293T/17, HeLa, and NIH 3T3 cell lines. Characterization of internalization of DNA by confocal microscopy and measurements of the zeta potentials of lipoplexes suggested that these large differences in cell transfection result from (i) differences in the extents to which these lipoplexes are internalized by cells and (ii) changes in the oxidation state of BFDMA that occur in the extracellular environment (i.e., prior to internalization of lipoplexes by cells). Characterization of lipoplexes by small-angle neutron scattering (SANS) and by cryogenic transmission electron microscopy (cryo-TEM) revealed changes in the nanostructures of lipoplexes upon the addition of ascorbic acid, from aggregates that were generally amorphous, to aggregates with a more extensive multilamellar nanostructure. The results of this study provide guidance for the design of redox-active lipids that could lead to methods that enable spatial and/or temporal control of cell transfection.